The optimisation rule for investment in mining projects - Foo, N.; Bloch, Harry; Salim, Ruhul (Pergamon Press, 2017)
Investment in mining projects involves significant uncertainty. Project investment is usually high risk, irreversible and challenged by major economic factors. Mining commodity prices in particular always show greater volatility than any other primary products. The variation of these prices is critical in the investment decision of whether the project should go ahead, be abandoned or be delayed. This paper examines the impact of mineral price uncertainty on mining investment decisions using examples of projects in the Asia-Pacific region. Applying the mean reversion (MR) model, the commodity trigger value for investment decisions in each project is determined in the context of operational flexibilities. The findings indicate it is sometimes better to wait for a more suitable time to invest.